On Subadditivity of Functions on Positive Operators Without Operator Monotonicity and Convexity - ehsan anjidani (پژوهش‌های ریاضی, 2020)
‎‎‎‎In ‎this ‎paper, ‎we ‎investigate ‎the ‎subadditivity ‎of ‎functions ‎on positive ‎operators ‎without ‎operator ‎monotonicity ‎and ‎operator ‎convexity: Let ‎‎$‎A‎$ ‎and ‎$‎B‎$ ‎be positive operators on a Hilbert space ‎‎‎‎‎‎‎‎‎‎‎‎‎‎‎‎‎‎‎$‎‎mathcalH‎$ ‎satisfying‎ ‎‎$‎0leq AB+BA‎$. Suppose that for the operator